2014
DOI: 10.1111/iju.12582
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde flexible ureteroscopic approach of upper urinary tract pathology: What is the status in 2014?

Abstract: Abbreviations & AcronymsAbstract: Flexible uretero-renoscopy witnessed dramatic technological improvements, ultimately translating in more diverse indications, better instrument durability, procedural efficacy and safety. Diagnostic exploration of the upper urinary tract, treatment of selected cases of ureteral and especially pyelocaliceal stones, caliceal diverticulum and infundibular stenosis, treatment, and follow-up of upper urinary tract tumors are the main indications for this approach. We review the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Placing nephrostomy tube in pregnancy has similar complications. 12,16,17 In the study of Parulkar et al 4 20 all types of stones with varying compositions can be fragmented into relatively small particles which can be easily eliminated. 21 Holmium laser lithotripters compared with pneumatic lithotripters, produce weak shock waves with minimal tissue penetration, thus theoretically limiting the risk of fetal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placing nephrostomy tube in pregnancy has similar complications. 12,16,17 In the study of Parulkar et al 4 20 all types of stones with varying compositions can be fragmented into relatively small particles which can be easily eliminated. 21 Holmium laser lithotripters compared with pneumatic lithotripters, produce weak shock waves with minimal tissue penetration, thus theoretically limiting the risk of fetal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of stone migration is less when Holmium laser lithotripter was used. 20,21 Laing et al 22 reported a series review consisting of 116 pregnant women who underwent URS for ureteral stone treatment: holmium laser was used with success in 27 (23%) patients and a pneumatic lithotripter in 21 (18%) patients. This study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The main complications of RIRS consist of: fever, flank pain, urinary infection, transient hematuria, acute urinary retention, ureteral and pelvicalyceal abrasion, stone street, subcapsular hematoma, fornix rupture, extravasation, urinoma, ureter avulsion, bleeding requiring transfusion and sepsis (2, 3). Reported complication rates vary between 0% and 25% in different studies (1, 2, 4, 5).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Since the introduction of first flexible ureteroscopic procedures in 1960’s there have been many refinements in ureteroscopes in terms of image quality, durability and deflection capability (1). With the addition of working channel and irrigation systems to the ureteroscopes and the introduction of holmium: yttrium aluminium garnet (YAG) laser systems, flexible ureteroscopy (FU) has emerged as a choice for both diagnosis and treatment of urinary lithiasis and urothelial malignancies of the upper urinary tract (1, 2). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation